Discrimination or not? Romani children in Polish special schools and diagnoses of intellectual disability. Issue 1 (June 2019) - Grzymała-Moszczyńska, Joanna; Barzykowski, Krystian; Grzymała-Moszczyńska, Halina; Kosno, Magdalena; Dzida, Daniel
Abstract : This comparative article examines the cognitive and linguistic functioning of Roma children attending both mainstream and special primary schools in Poland. Although many studies have investigated the segregation of Romani children in education, only a few of these have used psychological diagnostic tests as a source of information about Roma children. Our research addresses this gap and is an attempt to provide answers about the current situation of Romani children in both special and mainstream schools in Poland. A mixed-method research design was employed and two studies were conducted. In the first study, 77 Roma children were tested using Raven's Progressive Matrices (RPM) and two language competence tests: a Pictorial Vocabulary Test – Understanding (receptive vocabulary) and a Pictorial Vocabulary Test (expressive vocabulary). In the second study, we interviewed 54 Roma parents and school personnel. The results of Study 1 show that among Roma children previously diagnosed with a mental disability, RPM results revealed that 19 percent were in fact of average intellectual ability, 52 percent were below average (9 percent borderline), and only 29 percent had a mild disability. The possible reasons for this were analysed in Study 2. Based on semi-structured interviews, the social context of Roma children's education is presented. Finally, we discuss the situation of Roma children in the Polish education system and make recommendations for modifications to current practice.